Research needs: issues and problems of talent working graduates university programs of engineering and technology - Muhamad Sanusi, Amanina; Puteh, Saifullizam; Hassan, Nur Farha (American Scientific Publisher, 2018)
Career nowadays require graduates with working experience in order to work optimally and orderly manner. Employers have certain requirements and criteria in selecting prospective employees such as academic graduates, soft skills, curriculum and good talent. The study was conducted with the aim of looking at the identify issues and problems in the industry related to university graduates programs of engineering and technology. This study uses structured partial interview instruments. This interview sessions were carried out with 2 people from the industry and 3 university graduates unemployed. This interview to run to see in terms of talent work required in the industry. The overall data interviews taken will transcript to identify issues and problems. The results show that the employer seeks students of engineering and technology talent to work before working in industry.